Nursing outcome quality indicators for patients with ischemic stroke receiving thrombectomy treatment: A Delphi study - Chaiyuth Kotalux; Thanpimol Kensakoo; Werayuth Srithumsuk (Belitung Nursing Journal, 2022)
Background: Thrombectomy treatment is a critical procedure that emerged a few years ago, and nurses play a crucial role in the process, particularly in preventing complications and improving outcomes. Therefore, determining the quality of nursing care with best-fit quality indicators in patients with ischemic stroke receiving thrombectomy is necessary. However, no research has determined the nursing outcome quality indicators for these patients. Objective: This research aimed to identify the nursing outcome quality indicators for patients with ischemic stroke receiving thrombectomy treatment. Methods: Nineteen experts involved with patients with ischemic stroke receiving thrombectomy treatment were recruited. The Delphi method was implemented with three rounds between October 2021 to February 2022. Medians and interquartile ranges were analyzed. Results: Twenty-eight nursing outcome quality indicators were developed and grouped into three components, including 1) pre-procedure (five indicators), 2) intra-procedure (six indicators), and 3) post-procedure (17 indicators). Conclusion: This study revealed that the post-procedure of thrombectomy treatment had a greater number compared to pre and intra-procedures. The quality indicators developed in this research are practical and appropriate for nursing practice to enhance the quality of nursing care for patients with ischemic stroke receiving thrombectomy treatment.